Wage dynamics, trade-related wage premia and productivity spillovers : evidence from the South African manufacturing sector - Hlatswayo, Ayanda (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.